Etnobotani Hibiscus tiliaceus In The Dayak Community Of Bakumpai Bagus Village Barito Regency Kuala - Dharmono; Mardiah, Siti; Utami, Nurul Hidayati (JURNAL BIOSHELL, 2022)
Hibiscus tiliaceus is one of the plants that is still used by the Bakumpai Dayak Community. The Hibiscus tiliaceus plant is one of the plants found in Bagus Village, Barito Kuala Regency and has the potential to be used as a source of ethnobotany learning. This study aims to examine the ethnobotanical aspects of the Hibiscus tiliaceus plant. And using a descriptive research approach with interviews with the community to describe the ethnobotany of the Hibiscus tiliaceus plant. The results of the descriptive study showed 6 ethnobotanical studies of the Hibiscus tiliaceus plant. The results of the analysis show that the botanical study has a habitus in the form of a tree, the ethno-pharmacological study of Hibiscus tiliaceus is used as a wound dressing for diabetics, the ethno-ecological study of Hibiscus tiliaceus based on the growing conditions that meet the optimal requirements, the ethno-socioanthropological study of Hibiscus tiliaceus is used as a bracelet. Legs and propulsion, ethno-economic studies Hibiscus tiliaceus is used as rope, wrapping peanuts/kuaci and firewood. the ethno-linguistic study of Hibiscus tiliaceus was given the name "new". Keywords: Ethnobotany, Hibiscus tiliaceus, Bakumpai Dayak Community